Sustainable building ventilation solutions with heat recovery from waste heat - Nourozi, Behrouz (KTH, Hållbara byggnader, 2019)
The energy used by building sector accounts for approximately 40% of the total energy usage. In residential buildings, 30-60% of this energy is used for space heating which is mainly wasted by transmission heat losses. A share of 20-30% is lost by the discarded residential wastewater and the rest is devoted to ventilation heat loss. The main objective of this work was to evaluate the thermal potential of residential wastewater for improving the performance of mechanical ventilation with heat recovery (MVHR) systems during the coldest periods of year. The recovered heat from wastewater was used to preheat the incoming cold outdoor air to the MVHR in order to avoid frost formation on the heat exchanger surface. Dynamic simulations using TRNSYS were used to evaluate the performance of the suggested air preheating systems as well as the impact of air preheating on the entire system. Temperature control systems were suggested based on the identified frost thresholds in order to optimally use the limited thermal capacity of wastewater and maintain high temperature efficiency of MVHR. Two configurations of air preheating systems with temperature stratified and unstratified tanks were designed and compared. A life cycle cost analysis further investigated the cost effectiveness of the studied systems. The results obtained by this research work indicated that residential wastewater had the sufficient thermal potential to reduce the defrosting need of MVHR systems (equipped with a plate heat exchanger) in central Swedish cities to 25%. For colder regions in northern Sweden, the defrosting time was decreased by 50%. The temperature control systems could assure MVHR temperature efficiencies of more than 80% for most of the heating season while frosting period was minimized. LCC analysis revealed that wastewater air preheating systems equipped with temperature stratified and unstratified storage tanks could pay off their costs in 17 and 8 years, respectively. QC 20190830